Analisis Kualitas Pendidikan SMP Untuk Mendukung Rancangan Pembangunan Jangka Panjang Daerah (RPJPD) DKI JAKARTA Dalam Sistem Pertahanan Negara - Nadine Rahma Aulia; Yusuf Ali; Herlina Tarigan (Pusat Riset dan Inovasi Nasional, 2025)
The quality of education is a strategic factor in supporting national development and strengthening the state defense system based on human resilience (human security). Excellent education not only produces highly competent human resources (HR) but also shapes character capable of facing global challenges. This study aims to analyze the quality of education in Junior High School (SMP) students in DKI Jakarta Province as part of efforts to support the DKI Jakarta Long-Term Regional Development Plan (RPJPD) 2025–2045, which emphasizes the development of superior human resources for non-military protection. The research method used is quantitative with a quantitative descriptive analysis approach. The research data were obtained from the Education Report Portal and the Minimum Competency Assessment Report (AKM) for Junior High School Education published by the DKI Jakarta Education Quality Assurance Agency (BPMP) and the Ministry of Education, Culture, Research, and Technology for the period 2022–2024. The research variables include literacy, numeracy, and student character. The research results indicate that the quality of junior high school education in Jakarta has significantly improved in literacy and numeracy, with the highest achievement reaching 98.26% in 2024. Student character also shows a positive trend, although it still requires ongoing strengthening to align with the goal of developing a Pancasila student profile. However, the research also found a decline in indicators of learning quality and school security climate, which can hinder the achievement of holistic educational goals. Overall, these findings indicate that improving the quality of junior high school education in Jakarta significantly contributes to the vision of the Jakarta Regional Medium-Term Development Plan (RPJPD), particularly in developing superior human resources with global competitiveness and resilience to non-military threats. The research recommendations emphasize the importance of strengthening character, improving the quality of learning, and fostering a safe and conducive school climate.